Evaluation of the anti-inflammatory and antioxidant potential of the stem bark extract and some constituents of Aidia genipiflora (DC.) dandy (rubiaceae) - Daniel Anokwah; Evelyn Asante Kwatia; Isaac Kingsley Amponsah; Yakubu Jibira; Benjamin Kingsley Harley; Elvis Ofori Ameyaw; Ernest Obese; Robert Peter Biney; Abraham Yeboah Mensah (Heliyon, 2022)
Aidia genipiflora (DC.) Dandy (Rubiaceae) is used to treat various microbial and inflammatory conditions by traditional healers in West African countries. However, there is no information on anti-inflammatory potential of A. genipiflora. This work therefore provides information on the anti-inflammatory and the antioxidant activities of the stem bark extracts and some bioactive constituents of Aidia genipiflora. Method: The anti-inflammatory activities of the extracts and compounds from A. genipiflora were investigated using the carrageenan-induced footpad oedema assay and the egg albumin denaturation assay. The antioxidant activities of the extract and compounds were investigated using the DPPH radical scavenging assay and the phosphomolybdenum total antioxidant capacity assay. The whole extract of A. genipiflora was also investigated for its acute oral toxicity using the fixed-dose procedure described by the Organization for Economic Cooperation Development guidelines. Result: The whole extract showed no acute toxicity effect and the LD50 was estimated to be greater than 3000 mg/kg body weight. The whole extract, methanol, and ethyl acetate fractions (30, 100, and 300 mg/kg) showed in vivo anti-inflammatory activity with respective percentage inhibition of oedema of 45.11 ± 3.41, 31.12 ± 3.42 and 29.28 ± 3.58 (p < 0.001) at the highest dose of 300 mg/kg. Diclofenac, used as a reference drug, gave a % inhibition of 48.94 ± 3.58. The compounds isolated from A. genipiflora demonstrated in-vitro anti-inflammatory activity at the IC50 range (16–96 μg/mL) compared to diclofenac (IC50 of 74.48 μg/mL). Oleanonic acid (AG1) and D-mannitol (AG4) further demonstrated in vivo anti-inflammatory activity (ED50 = 20.61 ± 1.29; 23.51 ± 1.26 mg/kg respectively) which was less potent compared to diclofenac (ED50 = 12.50 ± 1.41 mg/kg) in the carrageenan-induced oedema assay. The whole extract, pet. ether, ethyl acetate, and methanol fractions of A. genipiflora exhibited DPPH scavenging activities with respective IC50 of 222.2, 169.7, 121.5, and 40.7 μg/mL. The whole extract of A. genipiflora exhibited considerable total antioxidant capacity with respective values of 248.5 mg/g of ascorbic acid equivalent. All the compounds exhibited low DPPH scavenging activity with IC50 (64–86 μg/mL), compared to ascorbic acid (IC50 of 3.13 ± 1.20 μg/mL). These results highlight the anti-inflammatory and antioxidant activities of Aidia genipiflora stem bark extract and its constituents as evidence to support its traditional uses.